Positive electrode and lithium secondary battery manufactured using same

By adding lithium nickel manganese and cobalt composite oxide materials to the lithium iron phosphate positive electrode active material layer and controlling its particle size ratio, the problem of poor calendering performance of lithium iron phosphate positive electrode is solved, and high load and high energy density are achieved lithium secondary battery.

CN119404330APending Publication Date: 2025-02-07LG ENERGY SOLUTION LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380048584.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-11-06
Filing Date
2023-11-07
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The calendering performance of the lithium iron phosphate positive electrode is poor, which makes it difficult to significantly reduce the thickness of the positive electrode active material layer during the calendering process, and the calendering performance further decreases as the electrode load increases.

Method used

The second positive electrode active material of lithium nickel manganese cobalt composite oxide is added to the positive electrode active material layer, and its average particle size is controlled to be more than 3 or more than the average particle size of the first positive electrode active material, and the content of the second positive electrode active material is 10 weights %the following.

Benefits of technology

By improving the calendering performance, increasing the loading of the positive electrode, and significantly reducing the thickness of the positive electrode active material layer, thereby providing a high energy density lithium iron phosphate positive electrode and lithium secondary battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The positive electrode according to the present invention is a positive electrode including a positive electrode active material layer formed on a positive electrode current collector, in which the positive electrode active material layer includes a first positive electrode active material based on a lithium iron phosphate compound and a second positive electrode active material based on a lithium nickel manganese cobalt composite oxide, the second positive electrode active material is 10 wt% or less based on the total weight of the first positive electrode active material and the second positive electrode active material, and the ratio (= B / A) of the average particle diameter (D50) B of the second positive electrode active material to the average particle diameter (D50) A of the first positive electrode active material is 3 or more. The positive electrode according to one embodiment of the present invention has an effect of providing a lithium iron phosphate-based positive electrode having high energy density by increasing the capacity of the positive electrode due to improved calendering performance and significantly reducing the thickness of the positive electrode active material layer by calendering.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application claims the benefit of priority of Korean Patent Application No. 10-2022-0147050 filed on November 7, 2022 and Korean Patent Application No. 10-2023-0152112 filed on November 6, 2023.

[0002] The present invention relates to a positive electrode and a lithium secondary battery, and more particularly to a positive electrode having improved rolling performance and comprising a positive electrode active material of a lithium iron phosphate compound type, and to a lithium secondary battery. Background Art

[0003] As the technology of electric vehicles and energy storage systems (ESS) and the demand for them increase, the demand for batteries as energy sources has increased rapidly, and therefore, various studies have been conducted on batteries that can meet various needs. In particular, active research is being conducted on lithium secondary batteries with high energy density and excellent life and cycle characteristics as power sources for such devices.

[0004] As a positive electrode active material of a lithium secondary battery, lithium cobalt oxide (LCO), lithium nickel cobalt manganese oxide (LNCMO), lithium iron phosphate (LFP), and the like have been used.

[0005] Lithium iron phosphate is cheap because it is abundant in resources and contains low-cost material iron. In addition, because lithium iron phosphate has low toxicity, environmental pollution can be reduced when lithium iron phosphate is used. In addition, because lithium iron phosphate has an olivine structure, it can stably maintain an active material structure at high temperatures compared to lithium transition metal oxides having a layered structure. Therefore, it has the advantages of excellent high temperature stability of the battery and excellent high temperature life characteristics.

[0006] However, compared with the positive electrode active materials of lithium cobalt oxide and lithium nickel cobalt manganese oxide, lithium iron phosphate has a relatively low tap density and poor rolling performance, making it difficult to significantly reduce the thickness of the positive electrode active material layer during rolling. On the other hand, with the increase in demand for high energy density lithium secondary batteries, the load of the electrode has increased, but when the load of the electrode increases, the rolling performance decreases, so it is necessary to develop a technology to improve the rolling performance to achieve a high load of the lithium iron phosphate positive electrode. Summary of the invention

[0007] [Technical issues]

[0008] The present invention seeks to provide a lithium iron phosphate cathode having high energy density by improving rolling performance.

[0009] [Technical solution]

[0010] According to an exemplary embodiment of the present invention, there is provided a positive electrode, the positive electrode comprising a positive electrode active material layer formed on a positive electrode current collector, wherein

[0011] The positive electrode active material layer comprises a first positive electrode active material of a lithium iron phosphate compound and a second positive electrode active material of a lithium nickel manganese cobalt composite oxide, wherein

[0012] The second positive electrode active material is 10 wt % or less based on the total weight of the first positive electrode active material and the second positive electrode active material, and

[0013] The average particle size of the second positive electrode active material (D 50 ) B and the average particle size of the first positive electrode active material (D 50 ) The ratio of B to A (=B / A) is 3 or more.

[0014] In an exemplary embodiment, the average particle size (D 50 ) B and the average particle size of the first positive electrode active material (D 50 ) A ratio (=B / A) can be 4 to 15.

[0015] In an exemplary embodiment, the average particle size (D 50 ) B and the average particle size of the first positive electrode active material (D 50 ) A ratio (=B / A) can be 6 to 12.

[0016] In an exemplary embodiment, the content of the second positive electrode active material may be 5 wt % or less based on the total weight of the first positive electrode active material and the second positive electrode active material.

[0017] In an exemplary embodiment, the first positive electrode active material may have an average particle size (D 50 ).

[0018] In an exemplary embodiment, the first positive active material may have an average particle size (D 50 ).

[0019] In an exemplary embodiment, the second positive active material may have an average particle size (D 50 ).

[0020] In an exemplary embodiment, the first positive active material may be a compound represented by Chemical Formula 1 below.

[0021] [Chemical formula 1]

[0022] Li 1+a Fe 1-x Mx (PO 4-b )X b

[0023] (In Chemical Formula 1, M comprises one or more elements selected from Al, Mg, Ni, Co, Mn, Ti, Ga, Cu, V, Nb, Zr, Ce, In, Zn, and Y; X comprises one or more elements selected from F, S, and N; and a, b, and x are -0.5 ≤ a ≤ 0.5, 0 ≤ b ≤ 0.1, and 0 ≤ x ≤ 0.5, respectively)

[0024] In an exemplary embodiment, the second positive electrode active material may be a compound represented by Chemical Formula 2 below.

[0025] [Chemical Formula 2]

[0026] Li a Ni 1-x-y Co x Mn y M1 z M2 w O2

[0027] (In Chemical Formula 2, M1 comprises any one or more elements selected from W, Mo, and Cr; and M2 comprises any one or more elements selected from Al, Zr, Ti, Mg, Ta, and Nb, where 0.95 ≤ a ≤ 1.5, 0 < x ≤ 0.5, 0 < y ≤ 0.5, 0 ≤ z ≤ 0.03, 0 ≤ w ≤ 0.02, and 0 < x + y ≤ 0.7)

[0028] In an exemplary embodiment, the first positive electrode active material may further include a carbon coating on its surface.

[0029] In an exemplary embodiment, the first positive electrode active material may have a single body structure including primary particles.

[0030] In an exemplary embodiment, the porosity according to Formula 1 below may be 24% to 30%.

[0031] [Formula 1]

[0032] Porosity (%) = {1 - (measured density of the positive electrode active material layer / true density of the positive electrode active material)} × 100

[0033] In an exemplary embodiment, the loading amount of the positive electrode active material layer may be in the range of 400 to 700 mg / 25 cm 2 of the range.

[0034] According to another exemplary embodiment of the present invention, a lithium secondary battery is provided, the lithium secondary battery comprising: a positive electrode; a negative electrode; a separator between the positive electrode and the negative electrode; and an electrolyte. The positive electrode comprises a positive electrode active material layer formed on a positive electrode current collector, wherein

[0035] The positive electrode active material layer comprises a first positive electrode active material of a lithium iron phosphate compound and a second positive electrode active material of a lithium nickel manganese cobalt composite oxide, wherein

[0036] The second positive electrode active material is 10 wt % or less based on the total weight of the first positive electrode active material and the second positive electrode active material, and

[0037] The average particle size of the second positive electrode active material (D 50 ) B and the average particle size of the first positive electrode active material (D 50 ) The ratio of B to A (=B / A) is 3 or more.

[0038] [Beneficial Effects]

[0039] According to the positive electrode of the exemplary embodiment of the present invention, the positive electrode loading amount can be increased due to the improved rolling performance, and the thickness of the positive electrode active material layer can be significantly reduced by rolling, thereby providing a high-load lithium iron phosphate positive electrode and a high energy density lithium secondary battery. DETAILED DESCRIPTION

[0040] From the exemplary embodiments described in detail below, the advantages and features of the present invention and the methods for implementing the present invention will be apparent. However, the present invention is not limited to the exemplary embodiments described below and may be implemented in various different forms. On the contrary, the embodiments provided are intended to make the content of the present invention sufficient and complete and to fully inform those of ordinary skill in the art to which the present invention belongs, and the present invention is limited only by the scope of the claims.

[0041] Unless otherwise defined, all terms (including technical or scientific terms) used in this article should be interpreted as having the same meaning as commonly understood by ordinary technicians in the field to which the present invention belongs. In addition, unless so clearly defined, those terms such as those defined in commonly used dictionaries should not be interpreted in an ideal or overly formal sense.

[0042] The terms used herein are intended to describe embodiments, rather than to limit the present invention. In this specification, unless the context otherwise requires, the singular includes the plural. The words "comprising" and / or "including" as used in the specification do not exclude the presence or addition of one or more other ingredients in addition to the above-mentioned ingredients.

[0043] In the present specification, when any part is referred to as including any component, unless there is a specific description to the contrary, it does not mean to exclude any other component but includes additional components.

[0044] In this specification, reference to "A and / or B" means A, B, or A and B.

[0045] In the present specification, "%" means weight % unless otherwise specifically stated.

[0046] In this manual, D 50 Refers to the particle size corresponding to 50% of the cumulative volume in the particle size distribution curve. 50 It can be measured, for example, by laser diffraction, which is generally capable of measuring particle sizes ranging from submicrometers to several millimeters, and can obtain results with high reproducibility and high resolution.

[0047] In this specification, the "specific surface area" is measured by the Brunauer-Emmet-Teller (BET) method, and specifically can be calculated from the nitrogen adsorption amount at liquid nitrogen temperature (77 K) using BELSORP-mini II available from BEL Japan.

[0048] In this specification, "weight average molecular weight (Mw)" refers to a conversion value relative to standard polystyrene measured by gel permeation chromatography (GPC). Specifically, the weight average molecular weight is a value obtained by converting a value measured using GPC under the following conditions, and a calibration curve is prepared using standard polystyrene of an Agilent system.

[0049] <Measurement conditions>

[0050] Measuring instrument: Agilent GPC (Agilent 1200 series, USA)

[0051] Column: Two connected PL mixed B

[0052] Column temperature: 40°C

[0053] Eluent: Tetrahydrofuran

[0054] Flow rate: 1.0 mL / min

[0055] Concentration: ~1 mg / mL (100 μL injection)

[0056] Hereinafter, the present invention will be described in detail.

[0057] positive electrode

[0058] The positive electrode for a lithium secondary battery according to an exemplary embodiment of the present invention is a positive electrode including a positive electrode active material layer formed on a positive electrode current collector, wherein

[0059] The positive electrode active material layer comprises a first positive electrode active material of a lithium iron phosphate compound and a second positive electrode active material of a lithium nickel manganese cobalt composite oxide, wherein

[0060] The second positive electrode active material is 10 wt % or less based on the total weight of the first positive electrode active material and the second positive electrode active material, and

[0061] The average particle size of the second positive electrode active material (D 50 ) B and the average particle size of the first positive electrode active material (D 50 ) The ratio of B to A (=B / A) is 3 or more.

[0062] Lithium iron phosphate compound positive electrode active materials have low tap density, which makes it difficult to significantly reduce the thickness of the positive electrode active material layer when rolling the lithium iron phosphate positive electrode. As a result of repeated studies to solve these problems, the inventors found that when a small amount of lithium nickel manganese cobalt composite oxide second positive electrode active material having a better tap density than the first positive electrode active material is added, and when the average particle size (D 50 ) B and the average particle size of the first positive electrode active material (D 50 ) When the ratio of B to A (=B / A) is controlled at a predetermined ratio, the rolling performance of the positive electrode is surprisingly improved, thereby completing the present invention.

[0063] The positive electrode according to one embodiment of the present invention can increase the loading amount of the positive electrode due to improved rolling performance, and can significantly reduce the thickness of the positive electrode active material layer by rolling, thereby having the effect of providing a high energy density positive electrode.

[0064] A positive electrode according to one embodiment of the present invention may include a positive electrode current collector and a positive electrode active material layer disposed on at least one side of the positive electrode current collector.

[0065] The positive electrode current collector may be, but is not limited to, any conductive material that does not cause chemical changes in the battery, such as stainless steel, aluminum, nickel, titanium, calcined carbon, or aluminum or stainless steel whose surface has been treated with carbon, nickel, titanium, silver, etc.

[0066] The thickness of the positive electrode current collector may be 3 μm to 500 μm, and fine concavoconvexities may also be formed on the surface of the positive electrode current collector to increase the adhesion to the positive electrode active material layer. For example, it may be used in various forms such as a film, a sheet, a foil, a net, a porous material, a foam, a non-woven fabric material, etc.

[0067] The positive electrode active material layer may include a lithium iron phosphate compound-based first positive electrode active material and a lithium nickel manganese cobalt composite oxide-based second positive electrode active material, and may further include a binder, a conductive material, a dispersant, and the like.

[0068] Each component contained in the positive electrode active material layer is described in detail below.

[0069] The present invention provides a positive electrode active material, which comprises: a first positive electrode active material, which is a lithium iron phosphate compound type positive electrode active material; and a second positive electrode active material, which is a lithium nickel manganese cobalt composite oxide type positive electrode active material.

[0070] According to the exemplary embodiment, the first positive active material may be a compound represented by Chemical Formula 1 below.

[0071] [Chemical formula 1]

[0072] Li 1+a Fe 1-x M x (PO 4-b )X b

[0073] (In Chemical Formula 1, M includes one or more elements selected from Al, Mg, Ni, Co, Mn, Ti, Ga, Cu, V, Nb, Zr, Ce, In, Zn, and Y,

[0074] X contains one or more elements selected from F, S and N, and

[0075] a, b and x are -0.5≤a≤0.5, 0≤b≤0.1 and 0≤x≤0.5 respectively)

[0076] For example, the first positive active material may be LiFePO 4 .

[0077] The first positive electrode active material may be a primary particle or a secondary particle in which primary particles are aggregated together, and preferably has a single body structure including the primary particles.

[0078] In the present invention, "monolith structure" refers to a structure in which particles are not aggregated together and exist in morphologically independent phases. The particle structure in contrast to the monolith structure may include a structure in which relatively large-sized particle shapes (secondary particles) are formed by physical and / or chemical aggregation of relatively small-sized particles (primary particles).

[0079] When the first positive electrode active material has a single body structure consisting of primary particles, the possibility of lithium iron phosphate particle breakage during the rolling process is less than that of secondary particles, and thus the capacity reduction due to detachment of broken particles is smaller, which is preferred.

[0080] Furthermore, when the first positive active material has a single body structure composed of primary particles, during the drying process of the positive electrode slurry, migration of the binder may be alleviated, thereby improving the interface adhesion between the positive electrode collector and the positive active material layer.

[0081] In an exemplary embodiment, the first positive electrode active material may further include a carbon coating on the surface. When the carbon coating is formed on the surface of the lithium iron phosphate, electrical conductivity may be improved, thereby improving resistance characteristics of the positive electrode.

[0082] The carbon coating layer can be formed using at least one raw material selected from the group consisting of glucose, sucrose, lactose, starch, oligosaccharides, polyoligosaccharides, fructose, cellulose, polymers of furfuryl alcohol, block copolymers of ethylene and ethylene oxide, ethylene-based resins, cellulose-based resins, phenol-based resins, asphalt-based resins, and tar-based resins. Specifically, the carbon coating layer can be formed by mixing the raw materials with lithium iron phosphate and then heat-treating them.

[0083] In an exemplary embodiment, the average particle size D of the first positive electrode active material is 50 The average particle size D of the positive electrode active material may be 0.1 μm to 3.0 μm, preferably 0.5 μm to 1.5 μm, and more preferably 0.6 μm to 1.3 μm. 50 When the above range is met, the mobility of lithium in lithium iron phosphate can be improved, thereby improving the charge and discharge characteristics of the battery.

[0084] In an exemplary embodiment, the BET specific surface area of ​​the first positive electrode active material may be 5 m 2 / g to 20 m 2 / g, more specifically 7 m 2 / g to 18 m 2 / g, more specifically 9 m 2 / g to 16 m 2 When the above range is satisfied, aggregation of the first positive electrode active material can be effectively suppressed even in a positive electrode slurry composition having a relatively low dispersant content.

[0085] According to the exemplary embodiment, the second positive active material may be a compound represented by Chemical Formula 2 below.

[0086] [Chemical formula 2]

[0087] Li a Ni1-x-y Co x Mn y M1 z M2 w O2

[0088] (In Chemical Formula 2,

[0089] M1 contains any one or more elements selected from W, Mo, and Cr, and

[0090] M2 contains any one or more elements selected from Al, Zr, Ti, Mg, Ta, and Nb,

[0091] where 0.95 ≤ a ≤ 1.5, 0 < x ≤ 0.5, 0 < y ≤ 0.5, 0 ≤ z ≤ 0.03, 0 ≤ w ≤ 0.02, and 0 < x + y ≤ 0.7)

[0092] For example, the second positive electrode active material may be LiNi 0.6 Co 0.2 Mn 0.2 O2 or LiNi 0.8 Mn 0.1 Co 0.1 O2, etc., and any one or a mixture of two or more thereof may be used.

[0093] Compared with the lithium iron phosphate compound, the lithium nickel manganese cobalt composite oxide-based positive electrode active material represented by the above Chemical Formula 2 has a more excellent tap density and is used to improve the calendering performance of the positive electrode.

[0094] In an exemplary embodiment, the second positive electrode active material may include single particles of primary particles or may include secondary particles including a plurality of primary particles aggregated together. Herein, the primary particles may be uniform or non-uniform.

[0095] In an exemplary embodiment, the average particle diameter D of the second positive electrode active material 50 may be 3 μm to 20 μm, more particularly 3 μm to 18 μm, more particularly 4 μm to 15 μm. If the average particle diameter of the second positive electrode active material exceeds 20 μm, there is a possibility that sedimentation of the second positive electrode active material particles may occur during the preparation of the positive electrode slurry, and if the average particle diameter of the second positive electrode active material is less than 3 μm, the effect of improving the calendering performance may not be significant, which is not desirable.

[0096] In an exemplary embodiment, based on the total weight of the first positive electrode active material and the second positive electrode active material, the second positive electrode active material may be 10% by weight or less, more specifically 5% by weight or less, more specifically 0.01% by weight to 1% by weight.

[0097] The second positive electrode active material added to improve the rolling performance shows saturation of the rolling performance improvement effect at a level of 5 wt % to 10 wt % relative to the total weight of the first positive electrode active material and the second positive electrode active material. Therefore, considering the capacity characteristics, it is preferred to contain the second positive electrode active material at a level within the above numerical range.

[0098] In an exemplary embodiment, the average particle size (D 50 ) B and the average particle size of the first positive electrode active material (D 50 ) A ratio (=B / A) may have a value of 3 or more, more particularly 4 to 15, more particularly 6 to 12. If the average particle size (D 50 ) B and the average particle size of the first positive electrode active material (D 50 ) If the value of the ratio of A (=B / A) is less than 3, the effect of improving the rolling performance may be small, so the B / A value is preferably at least 3. In addition, the larger the B / A value, the smaller the limit rolling thickness and the limit rolling porosity of the positive electrode tend to be, but when the B / A value is 15 or more, the reduction level of the limit rolling thickness and the limit rolling porosity converges to a specific level, so that the B / A value is preferably within the above numerical range. Here, the limit rolling thickness refers to the thickness of the positive electrode active material layer and the porosity of the positive electrode active material layer when rolling as much as possible without causing damage to the positive electrode collector such as fracture.

[0099] The positive electrode active material layer may further include a binder, a conductive material, and a dispersant in addition to the above-mentioned first and second positive electrode active materials.

[0100] Binder is included to enhance the adhesion between positive active material particles and the adhesion of positive active material to current collector. Specific examples of such binders include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-to-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose and regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene rubber (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber or its various copolymers, and any one thereof or a mixture of two or more thereof can be used alone. Based on the gross weight of the positive active material layer, the content of the binder can be 1% to 30% by weight.

[0101] There is no particular limitation on the conductive material as long as it imparts conductivity without causing chemical changes in the battery, and may be, for example: graphite; carbon black-based materials such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, or thermal black; conductive fibers such as carbon fibers or metal fibers; fluorocarbons; metal powders such as aluminum powder or nickel powder; conductive whiskers such as zinc oxide or potassium titanate; conductive metal oxides such as titanium oxide; conductive materials such as polyphenylene derivatives, etc. Specific examples of commercially available conductive materials may include acetylene black-based products (available from Chevron Chemical Company, Denka Singapore Private Limited (Denka Black), and Gulf Oil Company), Ketjen black, EC series (available from Armak Company), Vulcan XC-72 (available from Cabot Company), Super P (available from Timcal Co., Ltd), etc. Preferably, the conductive material may be a carbon nanotube. When the conductive material is carbon nanotubes, the excellent conductive network of the carbon nanotubes can suppress the binder migration phenomenon in which the binder moves to the electrode surface when the electrode is dried, thereby further improving the interfacial adhesion between the positive electrode current collector and the positive electrode active material layer.

[0102] In an exemplary embodiment, the content of the conductive material in the positive electrode active material layer may be 0.3 wt % to 2.0 wt %, specifically 0.4 wt % to 1.5 wt %, more specifically 0.5 wt % to 1.3 wt %. When the content of the conductive material in the positive electrode active material layer satisfies the above range, the conductive network of the positive electrode is ensured, thereby improving the conductivity of the positive electrode.

[0103] The dispersant suppresses excessive aggregation of the first positive electrode active material in particular in the positive electrode slurry, and enables the first and second positive electrode active materials to be effectively dispersed in the prepared positive electrode active material layer.

[0104] The dispersant may include a hydrogenated nitrile copolymer. Specifically, the dispersant may be a hydrogenated nitrile copolymer.

[0105] Specifically, the hydrogenated nitrile copolymer can be: a copolymer comprising a structural unit derived from an α,β-unsaturated nitrile and a structural unit derived from a hydrogenated conjugated diene; or a copolymer comprising a structural unit derived from an α,β-unsaturated nitrile, a structural unit derived from a conjugated diene, and a structural unit derived from a hydrogenated conjugated diene. As an α,β-unsaturated nitrile monomer, for example, acrylonitrile, methacrylonitrile, etc. can be used, and they can be used alone or in a mixture of two or more thereof. As a conjugated diene monomer, for example, C4 to C6 conjugated diene monomers such as 1,3-butadiene, isoprene, 2,3-methylbutadiene, etc. can be used, and they can be used alone or in a mixture of two or more thereof.

[0106] More specifically, the hydrogenated nitrile copolymer can be a hydrogenated nitrile butadiene rubber (H-NBR). Here, the hydrogenated nitrile butadiene rubber can have a weight average molecular weight (Mw) of 10,000 g / mol to 100,000 g / mol, preferably 15,000 g / mol to 90,000 g / mol, more preferably 20,000 g / mol to 50,000 g / mol. When the hydrogenated nitrile butadiene rubber meets the above numerical range, the effect of suppressing the aggregation of the conductive material is more excellent, even when the conductive material is aggregated, because the aggregation is spherical rather than linear, compared with the case of the linear aggregation of the conductive material, the specific surface area of ​​the aggregated conductive material can be minimized. As a result, the surface area of ​​the positive electrode active material adjacent to the aggregated conductive material and not participating in the insertion / deinsertion reaction of lithium is minimized, so that the discharge resistance of the lithium secondary battery can be reduced.

[0107] Based on the total solid content of the positive electrode slurry composition, the content of the dispersant may be 0.1 wt % to 2.0 wt %, specifically 0.2 wt % to 1.8 wt %, more specifically 0.3 wt % to 1.6 wt %. When the content of the dispersant satisfies the above range, aggregation of the positive electrode active material can be suppressed, thereby preventing gelation of the positive electrode slurry composition.

[0108] In an exemplary embodiment, the positive electrode active material layer may include 94 to 98% by weight of the positive electrode active material, 0.5 to 2% by weight of the conductive material, 1.0 to 4.0% by weight of the binder, and 0.5 to 2% by weight of the dispersant. When the composition of the positive electrode active material layer satisfies the above range, the adhesion and conductivity of the electrode are ensured, and by increasing the active material content, the capacity and resistance performance of the lithium secondary battery including the positive electrode are improved.

[0109] The positive electrode according to the present invention can be manufactured according to a conventional positive electrode manufacturing method. Specifically, the positive electrode can be manufactured by preparing a positive electrode slurry comprising a first and a second positive electrode active material, a conductive material, a binder and / or a dispersant, applying the positive electrode slurry to a positive electrode current collector, and then drying and rolling.

[0110] Alternatively, the positive electrode may be prepared by casting the positive electrode slurry onto a separate support and then laminating a film obtained by peeling off the support onto a positive electrode current collector.

[0111] According to the present invention, the positive electrode active material layer is composed of a bimodal positive electrode active material, wherein the average particle size of the first positive electrode active material and the average particle size of the second positive electrode active material are different, so that the gaps between the particles of the second positive electrode active material with a larger average particle size can be filled with the first positive electrode active material with a smaller average particle size, and due to the presence of the second positive electrode active material with a higher tap density, it has an improved calendering density, thereby achieving high load / high energy density of the positive electrode.

[0112] The positive electrode according to the exemplary embodiment may have a porosity according to the following Formula 1 of 24% to 30%, specifically 24% to 29%, and more specifically 25% to 28%.

[0113] [Formula 1]

[0114] Porosity (%) = {1-(measured density of positive electrode active material layer / true density of positive electrode active material)} × 100

[0115] Compared with the porosity of the positive electrode mainly containing lithium iron phosphate compound-type positive electrode active materials as the positive electrode active material, the above porosity numerical range is at a reduced level. According to the present invention, because the rolling performance is improved, the density after rolling can be increased so that the porosity can be within the above numerical range.

[0116] In an exemplary embodiment, the loading amount of the positive electrode active material layer may be in the range of 400 to 700 mg / 25 mL, more specifically 450 to 700 mg / 25 mL, more specifically 500 to 650 mg / 25 mL. The loading amount is based on the loading amount of the positive electrode active material layer disposed on one side of the current collector. According to the present invention, even for a positive electrode comprising a positive electrode active material layer having the above-mentioned high loading level, the rolling performance is improved, so that while having the above-mentioned loading amount, the porosity according to Formula 1 can be 24% to 30%, particularly 24% to 29%, and more particularly 25% to 28%.

[0117] Lithium secondary battery

[0118] Next, a lithium secondary battery according to the present invention will be described.

[0119] A lithium secondary battery according to one embodiment of the present invention may include a positive electrode, a negative electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte.

[0120] In a lithium secondary battery, the positive electrode is the same as described above. For example, the positive electrode comprises a positive electrode active material layer formed on a positive electrode current collector, wherein

[0121] The positive electrode active material layer comprises a first positive electrode active material of a lithium iron phosphate compound and a second positive electrode active material of a lithium nickel manganese cobalt composite oxide, wherein

[0122] The second positive electrode active material is 10 wt % or less based on the total weight of the first positive electrode active material and the second positive electrode active material, and

[0123] The average particle size of the second positive electrode active material (D 50 ) B and the average particle size of the first positive electrode active material (D 50 ) The ratio of B to A (=B / A) is 3 or more.

[0124] The positive electrode has been previously described in detail, and thus a repeated description will be omitted.

[0125] For example, the negative electrode may be prepared by preparing a negative electrode-forming composition including a negative electrode active material, a negative electrode binder, and a negative electrode conductive material, and then coating the composition on a negative electrode current collector.

[0126] There is no particular limitation on the negative electrode active material, and any compound capable of reversibly inserting and deinserting lithium can be used. Specific examples thereof include: carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, amorphous carbon, high crystalline carbon, etc.; (semi)metallic materials capable of forming alloys with lithium such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, Al alloys, etc.; and composite materials comprising (semi)metallic materials and carbonaceous materials. In addition, examples of low crystalline carbon include soft carbon and hard carbon, and examples of high crystalline carbon include natural graphite, condensed graphite, pyrolytic carbon, mesophase pitch carbon fiber, mesophase carbon microbeads, mesophase pitch, and high temperature sintered carbon such as coke derived from petroleum or coal tar pitch, which can be used alone or as a mixture of two or more thereof. In addition, as a negative electrode active material, a lithium metal film can be used.

[0127] The negative electrode conductive material is used to impart conductivity to the electrode, and any conductive material that does not cause chemical changes in the battery and has conductivity can be used without particular limitation. Specific examples of negative electrode conductive materials include: graphite such as natural graphite, synthetic graphite, etc.; carbon materials such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, carbon fiber, carbon nanotubes, etc.; powders or fibers of metals such as copper, nickel, aluminum, silver, etc.; conductive whiskers such as zinc oxide, potassium titanate, etc.; conductive metal oxides such as titanium oxide, etc.; and conductive polymers such as polyphenylene derivatives, etc., which can be used alone or in mixtures of two or more thereof. Relative to the total weight of the negative electrode active material layer, the content of the negative electrode conductive material can generally be 1 to 30% by weight, specifically 1 to 20% by weight, and more specifically 1 to 10% by weight.

[0128] Negative electrode binders are used to enhance the adhesion between negative electrode active material particles and the adhesion between negative electrode active materials and negative electrode current collectors. Specific examples of negative electrode binders include polyvinylidene fluoride (PVdF), vinylidene fluoride-hexafluoropropylene copolymer (PVdF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene rubber (EPDM rubber), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber and various copolymers thereof, which can be used alone or in a mixture of two or more thereof. Relative to the total weight of the negative electrode active material layer, the content of the negative electrode binder can be 1% to 30% by weight, specifically 1% to 20% by weight, and more specifically 1% to 10% by weight.

[0129] On the other hand, there is no particular limitation on the negative electrode current collector as long as it does not cause chemical changes in the battery and has high conductivity. As the negative electrode current collector, for example, copper, stainless steel, aluminum, nickel, titanium, sintered carbon, or copper or stainless steel whose surface has been treated with carbon, nickel, titanium, silver, etc., aluminum-cadmium alloy, etc. can be used.

[0130] In addition, the negative electrode current collector may have a thickness of 3 to 500 μm, and like the positive electrode current collector, fine concavoconvexities may be formed on the surface of the negative electrode current collector to increase the binding force of the negative electrode active material. For example, the negative electrode current collector may be used in various forms including films, sheets, foils, nets, porous bodies, foams, nonwoven fabrics, etc.

[0131] On the other hand, as a separator in a lithium secondary battery, any separator commonly used as a separator in a lithium secondary battery can be used without particular limitation, and in particular, a separator that exhibits low resistance to the migration of electrolyte ions and has excellent electrolyte impregnation ability is preferred. Specifically, it is possible to use: a porous polymer film, for example, a porous polymer film formed by a polyolefin polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer; or a stacked structure having two or more layers thereof. In addition, conventional porous non-woven fabrics can be used, for example, non-woven fabrics formed by high melting point glass fibers or polyethylene terephthalate fibers. In addition, the separator can be a porous film having a pore size of 0.01 μm to 10 μm and a thickness of 5 μm to 300 μm.

[0132] On the other hand, in the lithium secondary battery, the electrolyte may contain an organic solvent and a lithium salt generally used in an electrolyte, and they are not particularly limited.

[0133] As the organic solvent, any solvent that can be used as a medium through which ions participating in the electrochemical reaction of the battery can migrate can be used without particular limitation. Specifically, as the organic solvent, ester solvents such as methyl acetate, ethyl acetate, γ-butyrolactone, ε-caprolactone, etc.; ether solvents such as dibutyl ether, tetrahydrofuran, etc.; ketone solvents such as cyclohexanone, etc.; aromatic hydrocarbon solvents such as benzene, fluorobenzene, etc.; or carbonate solvents such as dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC), propylene carbonate (PC), etc. can be used.

[0134] Among them, carbonate solvents are preferably used, and more preferably a mixture of cyclic carbonates such as ethylene carbonate or propylene carbonate with high ionic conductivity and high dielectric constant that can improve the charge and discharge performance of the battery and linear carbonate compounds with low viscosity (e.g., ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate, etc.) is used.

[0135] There is no particular restriction on the lithium salt, as long as it is a compound that can provide the lithium ions used in the lithium secondary battery. Specifically, as the lithium salt, LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI, LiB(C2O4)2, etc. can be used. The lithium salt is preferably contained in the electrolyte at a concentration of about 0.6 mol% to 2 mol%.

[0136] In order to improve the life characteristics of the battery, inhibit the reduction of the battery capacity, increase the discharge capacity of the battery, etc., in addition to the above-mentioned electrolyte components, the electrolyte may also contain one or more additives, such as pyridine, triethyl phosphite, triethanolamine, cyclic ether, ethylenediamine, (condensed) glycol dimethyl ether, hexamethylphosphoric triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted Oxazolidinone, N,N-substituted imidazoline, ethylene glycol dialkyl ether, ammonium salt, pyrrole, 2-methoxyethanol, aluminum chloride, etc. In this case, the content of the additive may be 0.1 wt % to 5 wt % relative to the total weight of the electrolyte.

[0137] The lithium secondary battery according to the present invention can be manufactured by inserting a separator between the positive electrode and the negative electrode to form an electrode assembly, placing the electrode assembly in a cylindrical battery case or a prismatic battery case, and injecting an electrolyte. Alternatively, the lithium secondary battery can be manufactured by stacking the electrode assemblies, impregnating the electrode assemblies with an electrolyte, placing the resultant in a battery case, and sealing the battery case.

[0138] In the manufacture of the lithium secondary battery according to the present invention, the electrode assembly may be dried to remove one or more organic solvents selected from the following: N-methyl-2-pyrrolidone (NMP), acetone, ethanol, propylene carbonate, ethyl methyl carbonate, ethylene carbonate and dimethyl carbonate used in the manufacture of the positive electrode. When an electrolyte having the same composition as the organic solvent used in the manufacture of the positive electrode is used as the electrolyte, the drying process of the electrode assembly may be omitted.

[0139] Unlike the above-described lithium secondary battery, a lithium secondary battery according to another embodiment of the present invention may be an all-solid-state battery.

[0140] As the battery case, any battery case commonly used in the art can be used, and there is no limitation on the external shape according to the use of the battery. For example, the external shape of the battery case can be a cylindrical shape using a can, a prismatic shape, a bag shape, a coin shape, etc.

[0141] The lithium secondary battery according to the present invention can be used in the following fields: portable devices such as mobile phones, laptop computers, digital cameras, etc.; energy storage systems (ESS); and electric vehicles such as hybrid electric vehicles (HEV), etc. because it stably exhibits excellent discharge capacity, output characteristics and capacity retention rate.

[0142] Hereinafter, the present invention will be described in more detail with reference to examples. However, the following examples are provided only to illustrate the present invention, and the scope of the present invention is not limited to the following examples.

[0143] Example 1: Preparation of positive electrode

[0144] The average particle size D of the first positive electrode active material 50 The average particle size D of the primary particles of the single body structure LiFePO4 and the second positive electrode active material is 1.0 μm. 50 The secondary particles of LiNi are 7 to 8 μm 0.6 Mn 0.2 Co 0.2 O2 was mixed in a weight ratio of 99.5:0.5 to prepare a positive electrode active material. Carbon nanotubes (CNT) as a conductive material, polyvinylidene fluoride (PVdF) as a binder, and hydrogenated nitrile rubber (HNBR) as a dispersant were added to N-methylpyrrolidone (NMP) solvent. A homogenizer was used to mix at 2500 rpm for 90 minutes to prepare a positive electrode slurry.

[0145] In the positive electrode slurry, the positive electrode active material, the conductive material, the binder and the dispersant were present in a weight ratio of 95:1.2:3.0:0.8, and the solid content of the positive electrode slurry was 62 wt %.

[0146] The cathode slurry was coated onto a 20 μm thick aluminum film to a concentration of 600 mg / 25 cm 2 , and then hot-air dried at 130° C. for 5 minutes, so that the positive electrode slurry has a solid content of 99.0 wt % or more (the thickness of the positive electrode active material after drying is about 140 μm).

[0147] Example 2: Preparation of positive electrode

[0148] A positive electrode was prepared by the same method as in Example 1, except that the weight ratio of the first positive electrode active material to the second positive electrode active material was changed to 99.9:0.1.

[0149] Example 3: Preparation of positive electrode

[0150] In addition to changing the average secondary particle size D of the second positive electrode active material 50 LiNi with a thickness of 4 to 5 μm 0.6 Mn 0.2 Co 0.2 A positive electrode was prepared by the same method as in Example 1 except for O2.

[0151] Example 4: Preparation of positive electrode

[0152] In addition to changing the average secondary particle size D of the second positive electrode active material 50 11 to 12 μm LiNi 0.6 Mn 0.2 Co 0.2 A positive electrode was prepared by the same method as in Example 1 except for O2.

[0153] Example 5: Preparation of positive electrode

[0154] In addition to changing the average secondary particle size D of the second positive electrode active material 50 14 to 15 μm LiNi 0.6 Mn 0.2 Co 0.2 A positive electrode was prepared by the same method as in Example 1 except for O2.

[0155] Example 6: Preparation of positive electrode

[0156] A positive electrode was prepared by the same method as in Example 1, except that the weight ratio of the first positive electrode active material to the second positive electrode active material was changed to 95:5.

[0157] Example 7: Preparation of positive electrode

[0158] A positive electrode was prepared by the same method as in Example 1, except that the weight ratio of the first positive electrode active material to the second positive electrode active material was changed to 90:10.

[0159] Comparative Example 1: Preparation of positive electrode

[0160] A positive electrode was prepared in the same manner as in Example 1, except that the weight ratio of the first positive electrode active material to the second positive electrode active material was changed to 100:0.

[0161] Comparative Example 2: Preparation of positive electrode

[0162] In addition to changing the average secondary particle size D of the second positive electrode active material 50 2 μm LiNi 0.6 Mn 0.2 Co 0.2 A positive electrode was prepared by the same method as in Example 1 except for O2.

[0163] Experimental example: Measurement of the ultimate rolling thickness and ultimate rolling porosity

[0164] For each positive electrode prepared in Examples 1-7 and Comparative Examples 1-2, the limiting rolled thickness and the limiting rolled porosity were measured and the results are shown in Table 1. In the method of measuring the limiting rolled thickness, the positive electrode was first rolled to a porosity of 30% according to the following formula 1, and if no cracks occurred in the current collector, it was rolled again to a porosity of 29%.

[0165] [Formula 1]

[0166] Porosity (%) = {1-(measured density of positive electrode active material layer / true density of positive electrode active material)} × 100

[0167] In this way, the positive electrode is rolled while gradually reducing the porosity, and the process is repeated until rupture occurs in the current collector, and the thickness of the positive electrode active material layer measured at the rolling level just before the rupture occurs is defined as the limiting rolling thickness, and the porosity at the rolling level just before the rupture occurs is defined as the limiting rolling porosity. For the limiting rolling porosity, the porosity of the positive electrode according to Comparative Example 1 is evaluated as 1, and the porosity of the positive electrode according to Examples 1-7 and Comparative Example 2 is described as a relative ratio relative to the porosity of the positive electrode according to Comparative Example 1.

[0168]

[0169] Compared with the positive electrode according to Comparative Example 1 not including the second positive electrode active material, the positive electrodes according to any one of Examples 1 to 7 all have a smaller ultimate rolling thickness and a smaller ultimate rolling porosity. In addition, compared with the positive electrode according to Comparative Example 1 including the second positive electrode active material but with an average particle size (D 50 ) B and the average particle size of the first positive electrode active material (D 50 ) A ratio (=B / A) of 2, the positive electrodes according to any one of Examples 1 to 7 all have a smaller limiting rolled thickness and a smaller limiting rolled porosity.

[0170] On the other hand, the positive electrode according to Example 6 in which the weight ratio of the second positive electrode active material is 5 weight % and the positive electrode according to Example 7 in which the weight ratio of the second positive electrode active material is 10 weight % have similar ultimate rolling thickness and ultimate rolling porosity, and it is analyzed that when the weight ratio of the second positive electrode active material is higher than a specific ratio, the improvement effect of rolling performance converges to a specific level.

[0171] In addition, since the positive electrode according to Example 4 and the positive electrode according to Example 5 have similar limiting rolled thickness and limiting rolled porosity, it is analyzed that when the average particle size (D 50 ) B and the average particle size of the first positive electrode active material (D 50 ) When the ratio of B to A (=B / A) exceeds a specific numerical range, the improvement level of calendering performance will not increase indefinitely, but will converge to a specific level.

[0172] Therefore, the cathode according to the present invention can provide a high-load cathode and a high-energy density lithium secondary battery by improving rolling performance in a cathode having 90 wt % or more of a lithium iron phosphate-based cathode active material as a cathode active material.

Claims

1. A positive electrode, the positive electrode comprising a positive electrode active material layer formed on a positive electrode current collector, wherein the positive electrode active material layer contains a first positive electrode active material of a lithium iron phosphate compound type and a second positive electrode active material of a lithium nickel manganese cobalt composite oxide type, wherein based on the total weight of the first positive electrode active material and the second positive electrode active material, the second positive electrode active material is 10% by weight or less, and The average particle size (D 50 ) B and the average particle size of the first positive electrode active material (D 50 )A ratio (=B / A) is 3 or more.

2. The positive electrode for a lithium secondary battery according to claim 1, wherein The average particle size (D 50 ) B and the average particle size of the first positive electrode active material (D 50 )A ratio (=B / A) is 4 to 15.

3. The positive electrode for a lithium secondary battery according to claim 2, wherein The average particle size (D 50 ) B and the average particle size of the first positive electrode active material (D 50 )A ratio (=B / A) is 6 to 12.

4. The positive electrode for a lithium secondary battery according to claim 1, wherein based on the total weight of the first positive electrode active material and the second positive electrode active material, the second positive electrode active material is 5% by weight or less.

5. The positive electrode for a lithium secondary battery according to claim 1, wherein The first positive electrode active material has an average particle size (D 50 ).

6. The positive electrode for a lithium secondary battery according to claim 1, wherein The first positive electrode active material has an average particle size (D) of 0.5 μm to 1.5 μm. 50 ).

7. The positive electrode for a lithium secondary battery according to claim 1, wherein The second positive electrode active material has an average particle size (D) of 3 μm to 20 μm. 50 ).

8. The positive electrode for a lithium secondary battery according to claim 1, wherein the first positive electrode active material is a compound represented by the following Chemical Formula 1: [Chemical Formula 1] Li 1+a Fe 1-x M x (PO 4-b )X b (In Chemical Formula 1, M contains one or more elements selected from Al, Mg, Ni, Co, Mn, Ti, Ga, Cu, V, Nb, Zr, Ce, In, Zn, and Y, X contains one or more elements selected from F, S, and N, and a, b, and x are -0.5 ≤ a ≤ 0.5, 0 ≤ b ≤ 0.1, and 0 ≤ x ≤ 0.5, respectively).

9. The positive electrode for a lithium secondary battery according to claim 1, wherein the second positive electrode active material is a compound represented by the following Chemical Formula 2: [Chemical Formula 2] Li a Ni 1-x-y Co x Mr y M1 z M2 w O2 (In Chemical Formula 2, M1 contains any one or more elements selected from W, Mo, and Cr, and M2 contains any one or more elements selected from Al, Zr, Ti, Mg, Ta, and Nb, in, 0.95 ≤ a ≤ 1.5, 0 < x ≤ 0.5, 0 < y ≤ 0.5, 0 ≤ z ≤ 0.03, 0 ≤ w ≤ 0.02, and 0 < x + y ≤ 0.7).

10. The positive electrode for a lithium secondary battery according to claim 1, wherein the first positive electrode active material further contains a carbon coating on the surface.

11. The positive electrode for a lithium secondary battery according to claim 1, wherein the first positive electrode active material has a single body structure including primary particles.

12. The positive electrode for a lithium secondary battery according to claim 1, wherein the porosity according to the following Formula 1 is 24% to 30%: [Formula 1] Porosity (%) = {1 - (measured density of the positive electrode active material layer / true density of the positive electrode active material)} × 100.

13. The positive electrode for a lithium secondary battery according to claim 1, wherein The loading amount of the positive electrode active material layer is 400 mg / 25 cm 2 Up to 700 mg / 25 cm 2 within the range.

14. A lithium secondary battery, the lithium secondary battery comprising: a positive electrode; a negative electrode; a separator interposed between the positive electrode and the negative electrode; and an electrolyte, wherein the positive electrode comprises: a positive electrode active material layer formed on a positive electrode current collector, wherein The positive electrode active material layer comprises a first positive electrode active material of a lithium iron phosphate compound and a second positive electrode active material of a lithium nickel manganese cobalt composite oxide, wherein The second positive electrode active material is 10 wt % or less based on the total weight of the first positive electrode active material and the second positive electrode active material, and The average particle size (D 50 ) B and the average particle size of the first positive electrode active material (D 50 )A ratio (=B / A) is 3 or more.

Citation Information

Patent Citations

  • Advanced wastewater treatment system with high efficiency

    KR1020220147050A

  • Resin composition, cured product, laminate, method for producing cured product, and semiconductor device, and polyimide precursor and method for producing same

    KR1020230152112A